(untitled) (ACME, 2021)
This paper depicts some not widely known aspects of the reconstruction of the Chiostro dei Morti and of the refettorio (refectory) of the Dominican priory adjacent to the church of Santa Maria delle Grazie, in Milan, both partly destroyed by bombing raids in august 1943. The refectory hosts the Last Supper by Leonardo da Vinci and the Crucifixion by Donato Montorfano. Some not very well known archive documents show the scope of the restoration work and the role played by the people who planned and executed works on these buildings, in an institutional or professional role, and the controversies these works raised, between 1943 and 1948. The events that unfolded during the planning of the restoration of the Last Supper, show significant similarities with what was going on in other restoration projects, among practical problems (not just technical ones), limits imposed by laws for the protection of historical buildings, intrinsic inconsistencies in the discipline, political and even personal conflicts, at the beginning of the complex and contradictory times of post-war reconstruction in Milan and in other places.